440 Modulating decreases in Superior Colliculus activity through optogenetic activation attenuates seizures in the WAG/Rij genetic model of Absence Epilepsy. (April 2022) - Palmer, Devin D.; Campos-Rodriquez, Carolina; Forcelli, Patrick A.
Abstract : OBJECTIVES/GOALS: While anti-seizure medications are effective, nearly one third of patients have seizures that go untreated. Prior studies using evoked seizure models have shown that activation of the Superior Colliculus (SC) display anti-seizure effects. Here we monitored and modulated the DLSC to suppress spontaneous seizures in a genetic model of epilepsy. METHODS/STUDY POPULATION: WAG/Rij rats (4 months old) were employed as study subjects. Animals were surgically prepared for virus injection (ChR2 excitatory opsin, or control vector), fiber optic implantation and cortical EEG for optogenetic studies. For In vivo electrophysiology, animals were implanted with a 16 wire multi-electrode array into the DLSC. In optogenetic experiments, we compared the efficacy of continuous neuromodulation to that of on-demand neuromodulation (real time detection of seizures) paradigms on a within-subject basis. We compared three stimulation frequencies on a within-subject basis (5, 20, 100 Hz). We quantified the number and duration of each spike wave discharge (SWD) during each two-hour-long trial. Electrode array single units were sorted and analyzed for activity before, during and after seizures. RESULTS/ANTICIPATED RESULTS: In vivo electrophysiology found there to be a significant decrease in single unit activity leading up to the start of SWDs. Interestingly, on-demand neuromodulation was effective in both females and males – where the greatest reduction in seizure duration was under 100 Hz light delivery. As expected, male and female animals injected with a control vector did not show a reduction in seizures in response to light delivery. In the open-loop (continuous) stimulation paradigm, optogenetic activation of the DLSC was without effect on the number or duration of SWDs at any of the frequencies examined. DISCUSSION/SIGNIFICANCE: SC activity is significantly decreased prior to the start of seizures. Furthermore, activation of the SC displays anti-seizure effects in a model of spontaneous seizures. A striking difference between open and closed-loop neuromodulation approaches underscores the importance of stimulation paradigm in determining therapeutic effect.